Control of tea aphids via attracting the parasitic wasp, Aphelinus sp. with synthetic semiochemicals - Wu, Yiqi; Han, Shanjie; Wang, Mengxin; Zhang, Qing-He; Han, Baoyu (Frontiers in Ecology and Evolution, 2022)
The tea aphid (Toxoptera aurantii Boyer de Fonscolombe) is an important tea plant pest insect worldwide. The parasitoid wasp, Aphelinus sp. is one of the most important natural enemies of the tea aphid in China. Unfortunately, Aphelinus sp. alone cannot effectively control the outbreaks of the aphid under natural conditions. In the current study, twenty-seven volatile compounds from the tea aphid-injured tea shoots, tea flowers, aphid sex pheromones or body rinses were selected and tested in Y-tube olfactometer assays for finding potential attractants of the parasitoid wasp, Aphelinus sp. Based on the Y-tube assay results, following three attractant mixtures were formulated and further tested in the field. Attractant-1 (HIPV-based) included trans-2-hexenal (10-6 g/ml), -ionone (10-6 g/ml), allyl isothiocyanate (10-4 g/ml), trans-2-pentenal (10-2 g/ml) and jasmone (10-2 g/ml) at equal loading volume of their solutions. Attractant-2 (with aphid sex-pheromone and body rinse compounds) included nepetalactone (10-6 g/ml), 2,5-hexanedione (10-4 g/ml), benzaldehyde (10-2 g/ml), eicosane (10-2 g/ml) and heptadecane (10-2 g/ml) at equal loading volume of their solutions. Attractant-3 (partial combination of Attractant-1 and Attractant-2) included nepetalactone (10-4 g/ml), benzaldehyde (10-2 g/ml), jasmone (10-2 g/ml), trans-2-hexenal (10-6 g/ml), eicosane (10-2 g/ml) and heptadecane (10-2 g/ml) at equal loading volume of their solutions. Field trials showed that Attractant-3 was much more attractive to the parasitic wasps than were the Attractant-1 and Attractant-2. From late August to late September the controlled-release of Attractant-3 effectively attracted Aphelinus sp. to parasitize and colonize the aphid populations in the treated tea plantations, resulting in a progressive decrease of the tea aphid abundances/populations in the fall. And the continuingly enhanced parasitism of overwintered aphids by Aphelinus sp. further reduced its population during the next spring tea harvest season. This approach may present an environmentally sound, non-insecticidal control tactic against the tea aphids using synthetic semiochemicals.